Modeling Services Liberalization: The Case of Kenya - Balistreri, Edward J. (2012)
This paper employs a 55 sector small open economy computable general equilibrium model of the Kenyan economy to assess the impact of the liberalization of regulatory barriers against foreign and domestic business service providers in Kenya. The model incorporates foreign direct investment in business services and productivity effects in imperfectly competitive goods and services markets endogenously, through a Dixit-Stiglitz framework. The ad valorem equivalent of barriers to foreign direct investment have been estimated based on detailed questionnaires completed by specialists in Kenya. We estimate very substantial gains to Kenya from regulatory liberalization in business services, and additional gains from uniform tariffs. The estimated gains increase to 50% of consumption in the long run steady state model, where the impact on the accumulation of capital from an improvement in the productivity of capital is taken into account. Decomposition exercises reveal that the largest gains to Kenya will derive from liberalization of costly regulatory barriers that are non-discriminatory in their impacts between Kenyan and multinational service providers.